Youth's Career Adaptability in Untung Jawa Island - Hawadi, Lydia Freyani; Winardy, Gary Collins Brata; Salma, Hasna Hafizhah (UI Scholars Hub, 2024)
The development of coastal regions is a pivotal aspect of Indonesia's ‘poros maritim dunia’ national agenda. This study focuses on Untung Jawa Island, a designated 'tourism village' off the coast of Jakarta, to investigate how the aspirations and perspectives of its young population align with this developmental drive. This study focuses on the viewpoints of the active Karang Taruna group members on the island, as they represent the youth engaged in community development. Utilizing a qualitative exploratory phenomenology design, this study employs Focused Group Discussions (FGD) to gain insights into how the youth perceive their potential career based on their career adaptability.